(untitled) (Brazilian Journal of Production Engineering, 2026)
The V Production Engineering Symposium of the Federal University of Catalão (UFCAT) is characterized as a teaching, research and extension event, with a national scope, whose target audience is made up of undergraduate and postgraduate students, professors, researchers, engineers and other professionals working in Production Engineering and related areas. V SIENPRO addresses the theme "Lean beyond manufacturing” and aims to identify experiences, promote discussions, generate scientific knowledge and produce ideas that contribute to the development of competitiveness strategies that allow increasing the efficiency of operations, through the application of innovations and intelligent production systems.